Neighborhood security boards and their relationship to the fight against common crime: case study of the Municipality of San Martín de Porres - Muñante Gomez, Pedro Jesus (2020)
Neighborhood councils, within citizen security, have become an organizational instrument that tries to avoid mutual mistrust between citizens and police, a matter of vital importance where there is a high presence of common crime in large cities, such as Metropolitan Lima. In this sense, this research aimed to determine to what extent the Neighborhood Citizen Security Boards are related to the fight against common crime in the district of San Martín de Porres. The study was descriptive-correlational and quantitative approach; while, the research design was non-experimental. The population was made up of the Neighborhood Councils of the San Martín de Porres district, whose number rises to 580 people with strategic responsibility and the sample was made up of 231 people. The data collection technique was direct observation, documentary review and survey; and the instruments used were bibliographic records and a Likert-type questionnaire. The results showed that the political and social support actions of community participation are fundamental to face the problems of citizen security. Therefore, it was concluded that the neighborhood citizen security boards have a high relationship in the fight against common crime in the district of San Martín de Porres, so it is necessary to optimize the level of management of the neighborhood citizen security boards in the district of San Martín de Porres, for having a high relationship in the control of common crime.